Evaluation of the manipulation that is given to the fishery product in terms of quality and safety at the time of its capture by the artisanal fisherman of the Gulf of Nicoya, Costa Rica - Chavarría Solera, Fabián (2017)
Artículo sobre la evaluación de la manipulación y almacenamiento que se le da al producto pesquero.